Feasibility of fluxless smelting of titaniferous magnetite ore in a pilot-plant open-arc DC furnace - Geldenhuys, Isabella Johanna (Stellenbosch : Stellenbosch University., 2020)
Thesis (MEng)--Stellenbosch University, 2020.